2021
DOI: 10.1080/09687637.2021.1933911
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not 9 to 5 recovery’: the role of a recovery community in producing social bonds that support recovery

Abstract: Aim: To understand how the social networks of a new recovery community can help sustain recovery, focusing on processes of social identity change, in the context of the wider UK recovery movement. Methods: A cross-sectional, mixed-methods social network analysis (SNA) of ego-network sociograms to map network transitions, using retrospective measures. Ten men were recruited from a peer-worker programme, in the South Ayrshire Alcohol and Drug Partnership (ADP), West of Scotland. Network measures were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
“…Activating non-substance using family and friends has shown to provide potential pathways to help persons with SUDs access and benefit from community support (154,155). Moreover, given that early recovery stages are sensitive periods for experiencing loneliness and social isolation (138), which has been associated with SUDs (156)(157)(158), adult offspring with SUDs may benefit from strategies to build and sustain prosocial connections and recovery-supportive networks (159), that prepare them for "normal everyday living" (137) and "outside living" in a way that promotes positive relational enactment.…”
Section: Discussionmentioning
confidence: 99%
“…All other papers in this special issue (Anderson et al, 2021;Dekkers et al, 2021;Frings et al, 2021;Gueta et al, 2020;Jason et al, 2021) focus on diverse recovery mediators and mechanisms and their role in individuals' recovery trajectories, reflecting the primary objective of the REC-PATH study.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
“…Overall, this special issue on addiction recovery mechanisms and mediators contributes to the growing evidencebase for providing recovery-oriented support in treatment and community settings (Ashford et al, 2020;Best, 2019) and disseminates knowledge and insights from recent research. First, several papers demonstrate that participation in selfhelp groups is crucial for initiating and maintaining recovery, not only through involvement in new, cohesive prosocial networks, but also through a strong commitment to sobriety (Anderson et al, 2021;Frings et al, 2021;Kougiali et al, 2021;. Developing 'the self' and a 'post-addiction' identity as well as social identification appear to be crucial elements in early recovery (Frings et al, 2021;Kougiali et al, 2021;Van Steenberghe et al, 2021).…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
See 1 more Smart Citation